Clinical grade production of IL‐15 stimulated NK cells for early infusion in adult AML patients undergoing haploidentical stem cell transplantation with post‐transplant cyclophosphamide. Issue 2 (13th January 2022) - Rubio‐Azpeitia, Eva; Pérez‐Corral, Ana Maria; Dorado‐Herrero, Nieves; Monsalvo, Silvia; Pérez‐Balsera, Gonzalo; Fernández‐Santos, Maria Eugenia; Kwon, Mi; Oarbeascoa, Gillen; Bastos‐Oreiro, Mariana; Falero, Carmen; Pascual Izquierdo, Cristina; Muñoz‐Martínez, Cristina; et al.
Abstract: Background: Allogeneic stem cell transplantation is the treatment of choice for acute myeloid leukemia (AML) patients. Unmanipulated haploidentical transplantation (Haplo‐HSCT) is commonly used for those AML patients who need a timely transplant and do not have a suitable matched donor, but relapse rates are still high, and improvements are needed. Adoptive immunotherapy using natural killer cells (NK cells) could be a promising tool to improved Haplo‐HSCT but, to date, no optimal infusion and manufacturing protocols have been developed. Study Design and Methods: In this study, we describe a quick and reproducible protocol for clinical‐grade production of haploidentical donor NK cells using double immunomagnetic depletion and enrichment protocol and overnight IL‐15 stimulation. Results: Thus, we have obtained 8 viable and functional NK cell products that have been safely infused to five AML patients undergoing unmanipulated Haplo‐HSCT. Discussion: Our results demonstrate the safety and feasibility of manufactured NK IL15 cells obtained from an adult allogeneic donor in the setting of haploidentical transplantation for AML patients.